RND-type Drug Efflux Pumps from Gram-negative bacteria: Molecular Mechanism and Inhibition - Venter, Henrietta; Mowla, Rumana; Ohene-Agyei, Thelma; Ma, Shutao (Frontiers in Microbiology, 2015)
Drug eﬄux protein complexes confer multidrug resistance on bacteria by transporting a wide spectrum of structurally diverse antibiotics. Moreover, organisms can only acquire resistance in the presence of an active eﬄux pump. The substrate range of drug eﬄux pumps is not limited to antibiotics, but it also includes toxins, dyes, detergents, lipids, and molecules involved in quorum sensing; hence eﬄux pumps are also associated with virulence and biofilm formation. Inhibitors of eﬄux pumps are therefore attractive compounds to reverse multidrug resistance and to prevent the development of resistance in clinically relevant bacterial pathogens. Recent successes on the structure determination and functional analysis of the AcrB and MexB components of the AcrAB-TolC and MexAB-OprM drug eﬄux systems as well as the structure of the fully assembled, functional triparted AcrAB-TolC complex significantly contributed to our understanding of the mechanism of substrate transport and the options for inhibition of eﬄux. These data, combined with the well-developed methodologies for measuring eﬄux pump inhibition, could allow the rational design, and subsequent experimental verification of potential eﬄux pump inhibitors (EPIs). In this review we will explore how the available biochemical and structural information can be translated into the discovery and development of new compounds that could reverse drug resistance in Gram-negative pathogens. The current literature on EPIs will also be analyzed and the reasons why no compounds have yet progressed into clinical use will be explored.